Roman gods : a conceptual approach - Lipka, Michael (Religions in the Graeco-Roman world ;, 2009)
Concerned with the question of how the concept of 'god' in urban Rome can be analyzed along the lines of six constituent concepts, that is space, time, personnel, function, iconography and ritual, this book develops general criteria for an analysis of pagan, Jewish and Christian concepts of gods in ancient Rome.